The experience of multi-cultural communication within a South African organization - Lesch, Anthea M (Rhodes University, Faculty of Humanities, Department of Psychology, 2000)
This research study was conducted in an attempt to explore the experience of multicultural communication within a South African organization. To this end employees, representing both Black and White culture, within a South African organization in the throes of transformation, were accessed. A model of managing diversity, focussing on the personal, interpersonal and organizational levels, was utilized in an attempt to uncover the nature of the experience of multi-cultural communication within Company X. A qualitative research design, and more specifically the case study method was employed in this study. Consistent with the case study approach a number of data sources were accessed. The primary data source consisted of a 3-stage interview process. Other data sources included documentary sources and company publications. By accessing multiple data sources, the researcher attempted to gain a holistic understanding of the experience of multi-cultural communication. It was found that the societal context of our post-Apartheid society exercises a profound influence on multi-cultural communication. Under Apartheid cultural separation was promoted. Diverse peoples thus have little common basis for interaction and view each other with skepticism and distrust. This exercises an effect on the personal and organizational levels of the managing diversity model. Influences at the personal level relate to the cultural paradigms of the individuals which provide the rules governing interactions and affect judgements of acceptable and unacceptable behaviours. Issues at the organizational level relate to its structures and policies which are still based on the "white is right ideology" . These issues, in turn, affect the interpersonal level of managing diversity, i.e., where the interactions occur, causing "communication short circuits" within the process of multi-cultural communication. In order to deal with failed multi-cultural communication, the individuals have developed a number of coping strategies. The results of the study indicate that both the organization and its employees share a responsibility for creating an environment that will facilitate effective multi-cultural communication.
Keywords: Intercultural communication -- South Africa; Communication in management -- South Africa; Communication in personnel management -- South Africa